Why, did I lose? Debriefing quality and its effects on justice, protests, and sales loss attributions. Issue 1 (January 2023) - Hawkins, Timothy G.; Wittmann, Mike; Gravier, Michael J.; Niranjan, Suman; Muir, William A.
Abstract: When suppliers lose in a competitive tender process, they need feedback to make accurate sales loss attributions and adjustments to their competitive strategy. Unfortunately, buyers seldomly provide sufficient feedback to enable diagnostics, learning, and adaptation. The purpose of this research is to explore a buyer's debriefing as an effective feedback mechanism. Based on data from a sample of 218 U.S. government source selections, a new construct, debriefing quality, is developed as a multi-dimensional construct comprised of: proposal efficacy information, procedural compliance and decision understanding information, and competitive intelligence information. Results show that debriefing quality enhances procedural justice and internal and external attributions and reduces supplier opportunism and perceptions of buyer opportunism. Further, the underlying procedural justice of the source selection deters bid protests, and debriefing quality can impact perceptions of procedural justice. Importantly, debriefing quality is essential in the assignment of loss attributions to strategy, thus affecting strategy change. These findings expand attribution theory by identifying new external attributions particular to a business-to-business context, namely suspicion of buyer opportunism and procedural justice. The study closes with specific information buyers can provide to suppliers to mitigate bid protests and help suppliers learn from the tender enabling future strategy improvements. Highlights: Buyers seldom provide feedback to enable supplier diagnostics, learning, and adaptation. This research explores a buyer's debriefing as an effective feedback mechanism. Procedural justice of source selection deters bid protests. Debriefing quality impacts perceptions of procedural justice and reduces supplier opportunism. Debriefing quality impact loss attributions to strategy, affecting strategy change.